Conceptions and knowledge about childhood in initial teacher training: Changes in recent decades and their impact on teacher professionality, and on schooling in childhood - Fátima Pereira (2009)
This paper looks at changes in the conceptions of childhood in recent decades, and their contribution to the understanding of the sociabilities and subjectivities that are moulded in school, and how these relate to teachers' initial training. An overview of social changes in late modernity is given, and their impact on teacher professionality and the conception of childhood considered. The results are given of a study on conceptions of childhood, expressed in or related to the initial training of teachers in the 1st Basic Education Cycle (CEB), in Portugal since April 1974. (C) 2009 Elsevier Ltd. All rights reserved.